CODE SWITCHING AND CODE-MIXING IN INTERNATIONAL SERVICE LEARNING ACTIVITIES AT UNIVERSITY OF TECHNOLOGY MALAYSIA - Cindy Margareta; Asropah; Suyoto (University of Kuningan, 2025)
This study explores the sociolinguistic and psycholinguistic dimensions of code-switching and code-mixing among participants in the International Service Learning (ISL) program at Kampung Jawa Batu, Malaysia. Employing a qualitative descriptive approach, the research investigates how multilingual speakers alternate between Malay, Indonesian, English, and Javanese to construct meaning, express identity, and foster intercultural understanding. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using Miles and Huberman’s (1994) qualitative data analysis framework. Findings reveal three dominant forms of language alternation: internal code-switching, external codeswitching, and code-mixing. Internal switching primarily signaled solidarity and cultural empathy, while external switching indexed professionalism and institutional authority through the strategic use of English. Code-mixing, often occurring intra-sententially, served affective and relational functions—expressing politeness, emotional warmth, and shared belonging. These practices reflect a dynamic interplay between linguistic creativity and social harmony, illustrating how multilingual speakers in ISL settings perform identity and negotiate meaning across cultural boundaries. The study concludes that code-switching and code-mixing in service-learning contexts extend beyond linguistic adaptation; they embody acts of empathy, inclusion, and intercultural collaboration. The findings contribute to broader discussions on multilingualism, translanguaging, and cross-cultural communication in global education.